Distinguishing between the board and management in company mission: implications for corporate governance - Bart, Christopher K.; Bontis, Nick; McMaster University, Michael G. DeGroote School of Business, Management of Innovation and New Technology Research Centre (My University, 2003)
A relationship between board/management "involvement" and "awareness" with organizational mission and their link to "employee commitment" and "organizational performance" was modeled by drawing on previous research. The model was tested with data from 339 large Canadian and US organizations. It was determined that "mission awareness" on the part of both the board and senior management is an important consideration in the determination of employees' commitment to the mission. However, the impact of board and management involvement with the mission is not identical. The results show especially the strong and important role that the board performs when it is actively engaged in the development of the organization's mission.
24 leaves : ; Includes bibliographical references (leaves 21-24). ;
Keywords: Mission statements; Mission awareness; Mission involvement; Corporate governance; Performance; PLS; Vision; Industrial management Mission statements Corporate governance